The impact of the COVID-19 pandemic on firm performance: Evidence from Thailand - Chancharat, Nongnit; Preecha, Sirinada; Chancharat, Surachai (International Journal of Management and Sustainability, 2023)
The worldwide economy has been greatly impacted by COVID-19 pandemic, and it has had a huge impact on the capital markets. This paper aims to investigate the impact of COVID-19 on the performance of companies listed on the Stock Exchange of Thailand (SET) using quarterly financial data of listed companies from 2016 to 2021 to predict corporate performance. The results show that the COVID-19 outbreak negatively impacted Thai firm performance, especially in the service, resource, real estate, and manufacturing industries, due to the implementation of a wide range of policies to control the spread of the virus. The findings support earlier research that the pandemic has had a serious negative impact on firm performance. However, uncertainty will remain until COVID-19 ends; policy implementations should facilitate these suffering industries in the short and long runs. This study addresses the research gap regarding the impact of COVID-19 on emerging economic activity from a firm-level perspective.